John Alexander Holm (1943-2015) - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2016)

Syntactic and lexical typology of Macau Patuá and Malacca Creole Portuguese. - Baxter, Alan N. (University of Saint Joseph, 2018)

Malacca Creole Portuguese in the 19th century: Evidence of a wider lectal range? - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2018)
Abstract Earlier linguistic research suggested that Malacca Creole Portuguese (MCP) had existed without diglossia with Portuguese ever since the Dutch conquest of Portuguese Malacca in 1642, yet it had experienced some contact with Portuguese in the 19th and 20th centuries. The present study adds significantly to this discussion. It considers a range of information from sociohistorical studies and archival sources (including linguistic data) relating to the Dutch (1642–1795, 1818–1823) and early British (1795–1818, 1823–1884) colonial periods. For the Dutch period, it is seen that contact with other Creole Portuguese communities is likely to have persisted for some time. Most significant, however, is the finding that 19th century texts in Portuguese and creole Portuguese, recently identified in archival sources in London and Graz, show that Portuguese continued to be part of the Malacca sociolinguistic setting until the early British period, and that missionary Indo-Portuguese also had a presence at that time. It is concluded that, rather than presenting a narrow lectal range akin to that of the MCP community in the late 20th century, the creole lectal grid in the 19th century was more complex, and included dimensions of a continuum in a diglossic relationship with Portuguese.
2 citations (Crossref) [2022-09-21] Publisher: John Benjamins

nventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country [Research Report] - Morais, Isabel; Baxter, Alan (University of Saint Joseph, 2018)

Grammar of Macao Creole Portuguese with Typological and Semiotic Considerations - Lebel, Alexandre (University of Saint Joseph, 2021)
Macao Creole Portuguese (MacCP) is a critically endangered language spoken in Southeastern China. The formation of MacCP is attributed to the speakers of Portuguese-based creole languages in Asia (Asian CPs), especially Papia Kristang, the Malayo-Portuguese of Malacca (MalCP). Since the 19th century, MacCP has been traditionally classified as Sino-Portuguese, but comparative methods incited some authors to treat MacCP within the Malayo-Portuguese group. In Macao, the Malaccan origin of MacCP, known as Patúa or Maquista, is generally underestimated or misunderstood by the local population, including the Macanese/Maquista community. The main goal of this research is to clarify the origin of MacCP from a typological perspective on grammatical features. Secondly, while considering a possible revitalization of Maquista, the research should assess the significance of the Malayo- and Sino-Portuguese classifications in popular narratives and relate the language to current practices. The grammar of MacCP emerged from the complex linguistic ecology of the Portuguese colonial expansion in Asia. The documentation of Asian CPs allows us to sketch possible scenarios that explain the formation of MacCP according to linguistic, historical and social factors. A digital corpus of MacCP containing archive documents, contemporary literature, and oral transcriptions was assembled in order to produce a systematic review of 130 grammatical features, as defined in the Atlas of Pidgin and Creole Language Structures Online (APiCS Online – Michaelis et al. [eds] 2013). MacCP and MalCP share certain features that are not found in South Asian CPs, such as the in situ position of interrogative words, the reduplication for nominal plural, the form of reciprocal constructions, and the verb serialization of motion constructions, thus pointing to the Malayo-Portuguese origin. At the same time, other features suggest a certain influence from Sinitic languages, mainly Cantonese and Hokkien, such as the convergence between the genitive, adjective and relative clause constructions, the double-object construction, the verb-neg-verb polar question, the copular focus construction, the reduplication inducing a change of word class or semantics, and the use of certain deontic, imperative, and prohibitive verbal markers. The comparative analysis of the grammars of MacCP, MalCP and other Asian CPs can be represented quantitatively by the means of a phylogenetic network (SplitsTree4 – Huson & Bryant 2006). The results clearly indicate that, from a structural perspective, MacCP belongs to the Malayo-Portuguese group and the presence of Sinitic elements did not affect the core of the grammar. In fact, MacCP and MalCP appear to be more similar to each other than to the former Malayo-Portuguese of Batavia. However, the Malayo-Portuguese classification of MacCP does not resonate with the Macanese community. By contrast, the Sino-Portuguese classification translates current linguistic, social and semiotic practices. A socio-semiotic survey among the millennial generation of Macanese and the consideration of themes and motifs in Maquista literature indicates that the revitalization of Maquista simultaneously implies, in their views, the preservation of the Cantonese and Portuguese heritage
Keywords: Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

Inventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country - Morais, Isabel; Baxter, Alan N. (University of Saint Joseph, 2018)
A study of Portuguese cultural vestiges assimilated into the local cultures of the island of Flores, in Eastern Indonesia, and maintained today. The vestiges include, principally, street theatre (the Bobo tradition) as well as ritual traditions inherited through the Confraternities established by Dominican missionaries in the 16th century.
Funded by Fundação Macau

Early Notices Regarding Creole Portuguese in Former Portuguese Timor - Baxter, Alan N.; Cardoso, Hugo C. (Journal of Language Contact, 2017)
4 citations (Crossref) [2022-09-21]

An Evaluation of the Treasure of Sacred Art of St. Joseph’s Seminary - Kwak, Maria Sheli (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Malacca Portuguese Creole - Pillai, Stefanie; Baxter, Alan N.; Soh, Wen-Yi (Journal of the International Phonetic Association, 2021)
Malacca Portuguese Creole (MPC) (ISO 639-3; code: mcm), popularly known as Malacca Portuguese or locally as (Papiá) Cristang, belongs to the group of Portuguese-lexified creoles of (South)east Asia, which includes the extinct varieties of Batavia/Tugu (Maurer 2013) and Bidau, East Timor (Baxter 1990), and the moribund variety of Macau (Baxter 2009). MPC has its origins in the Portuguese presence in Malacca, and like the other creoles in this subset, it is genetically related to the Portuguese Creoles of South Asia (Holm 1988, Cardoso, Baxter & Nunes 2012).
Publisher: Cambridge University Press